Method for manufacturing silicon nano particles and silicon-doped electrode material for battery
Through the grinding process, small-particle silicon nanoparticles are formed and a silicon oxide layer is formed on their surface. Combined with the use of dispersants and alkali liquid, the problem of volume expansion and agglomeration of silicon-based negative electrode materials is solved, and the battery capacity is significantly improved Maintenance and cycle life.
Patent Information
- Application Number
- CN202310959672.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2023-07-31
- Publication Date
- 2024-12-31
AI Technical Summary
The volume expansion of the silicon-based negative electrode material during charging and discharging is severe, resulting in poor material powdering and cycle life. The existing technology is difficult to effectively solve, limiting its application in batteries.
Through the grinding process, silicon nanoparticles with an average particle size of less than 200 nanometers are formed, and a silicon oxide layer is formed on their surface. Combined with the use of dispersants and alkali liquid, volume expansion and coalescence are suppressed, and the silicon-doped electrode material is enhanced. Cycle life.
It effectively improves the capacity maintenance rate of silicon-doped electrode materials under multiple charge and discharge cycles, and extends the service life of the battery.
Smart Images

Figure CN119218998A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing an electrode material, and in particular to a method for manufacturing silicon nanoparticles and silicon-doped electrode materials for batteries. Background Art
[0002] Currently, graphite is the mainstream negative electrode material for commercial lithium-ion batteries. However, its material development has approached the theoretical capacity of 372 mAh / g. For the demand for future high-energy density applications, the space that graphite can provide is quite limited.
[0003] As the next generation negative electrode material with the greatest potential, silicon-based negative electrodes have the advantage of high theoretical gram capacity (4200mAh / g). However, silicon has a dramatic volume expansion during the charging and discharging process, which leads to material pulverization and poor cycle life. Currently, it cannot be used alone as a negative electrode and is mostly mixed with graphite materials to form silicon-doped carbon electrode materials. In addition, based on battery stability considerations, the silicon content is about 3 to 5% of the total weight of the silicon-doped carbon electrode material.
[0004] Among the known solutions, the common silicon material size minimization processing technology is to use nano-scale silicon to control the volume expansion problem of large-size silicon. The size of silicon materials on the market is in the range of 10-300 nanometers (nm), but it is expensive. In addition, nano-scale silicon materials tend to aggregate into larger particles, which will make the process of uniform mixing to form electrodes more difficult.
[0005] Therefore, improving the existing process to produce silicon materials with improved volume expansion problems and increasing the cycle life of silicon-doped electrode materials are goals that the industry is eager to develop. Summary of the invention
[0006] The present invention is directed to a method for manufacturing silicon nanoparticles and silicon-doped electrode materials for batteries. The manufactured silicon nanoparticles for batteries have the advantage of improving volume expansion and can improve the retention rate of gram capacitance of silicon-doped electrode materials under multiple charge and discharge cycles.
[0007] The method for manufacturing silicon nanoparticles for batteries of the present invention comprises the following steps: mixing a dispersant and a solvent to form a dispersion liquid; then adding the dispersion liquid, grinding media and silicon raw materials into a grinder; performing a grinding process to form silicon nanoparticles with an average particle size of less than 200 nanometers; then taking out the silicon dispersion liquid containing silicon nanoparticles; then adding an alkali solution into the silicon dispersion liquid to form silicon nanoparticles for batteries, wherein the surface layer of the silicon nanoparticles for batteries is a silicon oxide layer.
[0008] In one embodiment of the present invention, the silicon raw material is recycled silicon material.
[0009] In one embodiment of the present invention, the dispersant is at least one selected from polyethylene glycol, polyvinyl oxadiazole, triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide and polyethylene glycol esters of fatty acids.
[0010] In one embodiment of the present invention, the solvent is water, an alcohol solvent or a ketone solvent.
[0011] In one embodiment of the present invention, based on 100 parts by weight of the silicon raw material, the amount of the dispersant added to the grinder is 10 to 50 parts by weight.
[0012] In one embodiment of the present invention, the grinding media is spherical in shape and has an average particle size of 100 to 500 nanometers.
[0013] In one embodiment of the present invention, based on 100 parts by weight of the silicon raw material, the amount of the grinding media added is 100 to 500 parts by weight.
[0014] In one embodiment of the present invention, the alkaline solution is a lithium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution.
[0015] In one embodiment of the present invention, based on 100 parts by weight of the silicon nanoparticles, the amount of the alkali solution added is 0.1 to 5 parts by weight.
[0016] In one embodiment of the present invention, the grinding process is a wet ball milling method, and the grinding time is 2 to 6 hours.
[0017] In one embodiment of the present invention, the ratio of the particle size of the silicon nanoparticles for batteries to the thickness of the silicon oxide layer is 3:1 to 40:1.
[0018] In one embodiment of the present invention, the thickness of the silicon oxide layer is 5 to 30 nanometers.
[0019] The method for manufacturing the silicon-doped electrode material of the present invention comprises the following steps: providing the above-mentioned silicon nanoparticles for battery; mixing the silicon nanoparticles for battery with an active material. The active material is a carbon material, a metal element or a metal alloy compound; and then spray granulation and calcination are performed to obtain the silicon-doped electrode material.
[0020] In one embodiment of the present invention, the content of the silicon nanoparticles for batteries is 1 to 40 weight % based on the total weight of the silicon-doped electrode material.
[0021] Based on the above, in the manufacturing method of silicon nanoparticles for batteries of the present invention, by adding a dispersant, the silicon nanoparticles are not easy to aggregate, thereby improving the grinding efficiency and promoting the miniaturization of silicon raw materials; by adding an alkaline solution, the surface of the silicon nanoparticles for batteries can have a silicon oxide film, thereby inhibiting the volume expansion of the silicon nanoparticles for batteries. The silicon-doped electrode material prepared by the silicon nanoparticles for batteries can effectively improve its gram capacity maintenance rate under multiple charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for producing silicon nanoparticles for batteries according to the present invention;
[0023] FIG. 2A to FIG. 2B This is the result of analyzing a slice of the silicon-doped carbon electrode material of the present invention by transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS). Figure 2A For electronic images, Figure 2B for Figure 2A Elemental composition analysis of the circled area.
[0024] Description of Reference Numerals
[0025] S102, S104, S106, S108, S110: steps. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are illustrative only, and the present invention is not limited thereto.
[0027] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as the arbitrary value and the smaller numerical range are written in the description text of the specification.
[0028] Figure 1 This is a flow chart of the method for producing silicon nanoparticles for batteries of the present invention. Figure 1 , proceed to step S102: mixing a dispersant and a solvent to form a dispersion. The dispersant may be, for example, an organic dispersant. Specifically, the dispersant may be selected from at least one of polyethylene glycol, polyvinyl oxadiazole, triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, a cellulose derivative, polyacrylamide, and polyethylene glycol ester of fatty acids, but is not limited thereto. The dispersant may also be, for example, a high molecular polymer, such as polyethylene glycol or polyvinyl oxadiazole. The solvent may be, for example, water, an alcohol solvent, or a ketone solvent.
[0029] Next, step S104 is performed: adding the dispersion liquid, grinding media and silicon raw material into the grinder. In this embodiment, the prepared dispersion liquid and grinding media are added into the grinder together, and then the silicon raw material is added. In some other embodiments, the dispersion liquid, grinding media and silicon raw material can also be added into the grinder together, and the present invention does not limit the order of feeding into the grinder.
[0030] In this embodiment, the silicon raw material may be recycled silicon obtained by purifying and recycling silicon waste. For example, the silicon waste may be discarded solar cells, IC panels, silicon wafer waste, and memory cards. Since the silicon raw material is recycled silicon material, it has the advantages of being environmentally friendly and low cost.
[0031] The grinding medium is used to grind the silicon raw material into silicon nanoparticles. The shape, size and material of the grinding medium are related to the properties of the material to be ground, the feed and the requirements of the product particle size. In the present embodiment, the shape of the grinding medium may be, for example, spherical, the average particle size (D50) may be, for example, 100 nanometers (nm) to 500 nanometers, and the material may be, for example, zirconium oxide, but is not limited thereto. The amount of grinding medium added is related to the size of the grinding chamber in the grinding machine and the content of the material to be ground. In some embodiments, based on 100 parts by weight of the silicon raw material added, the amount of grinding medium added may be, for example, 100 to 500 parts by weight. When the amount of grinding medium added is within the above range, the silicon raw material can be effectively ground into silicon nanoparticles of target particle size (for example, the particle size may be less than 200 nanometers) in the subsequent steps. When the amount of grinding medium added is less than 100 parts by weight, the area of the grinding medium contacting the material to be ground is low, resulting in a large amount of grinding time being consumed and poor grinding results. When the amount of grinding media added is greater than 500 parts by weight, in order to prevent the machine from being damaged during grinding, the dispersion must be over-diluted to fill the grinding chamber, which does not meet the solid content required for practical applications.
[0032] Dispersants can be used to disperse silicon nanoparticles to prevent them from agglomerating and agglomerating, making the whole too sticky to continue grinding, which helps to improve grinding efficiency. In some embodiments, the amount of dispersant added may be, for example, 10 to 50 parts by weight based on 100 parts by weight of silicon raw material. In other embodiments, preferably, the amount of dispersant added may be, for example, 20 to 40 parts by weight. When the amount of dispersant added is less than 10 parts by weight, the effect of preventing silicon nanoparticles from agglomerating and agglomerating may not be good. When the amount of dispersant added exceeds 50 parts by weight, subsequent purification may be difficult.
[0033] Next, step S106 is performed: a grinding process is performed to form silicon nanoparticles having an average particle size of less than 200 nanometers. In the present embodiment, the grinding process is a wet ball milling method, and the grinding time can be adjusted depending on the target particle size. Specifically, a particle size analyzer can be used to measure the average particle size of the current silicon particles during the grinding process. In some implementations, the grinding time can be, for example, 2 to 6 hours (h), but is not limited thereto. In addition, a dispersion liquid can also be added during the grinding process to improve the grinding efficiency. Here, the total amount of dispersant added (i.e., the sum of the dispersion liquid added to the grinder before and during grinding) does not exceed 50% by weight of the silicon raw material.
[0034] Next, step S108 is performed: taking out the silicon dispersion containing silicon nanoparticles.
[0035] Next, step S110 is performed: adding alkaline solution to the silicon dispersion to form silicon nanoparticles for batteries, and the surface layer of the silicon nanoparticles for batteries is a silicon oxide layer, and its thickness can be, for example, 5 nanometers to 30 nanometers. At this point, the manufacture of silicon nanoparticles for batteries has been completed. In this embodiment, the alkaline solution can oxidize the surface layer of the silicon nanoparticles to form silicon nanoparticles for batteries with a silicon oxide layer on the surface. The silicon oxide layer on the surface can inhibit the volume expansion of the silicon in the core, so that the electrode formed by doping other active materials (such as carbon materials, metal elements or metal compounds) for batteries can maintain its gram capacity after multiple charge and discharge cycles.
[0036] In detail, silicon has a theoretical capacity of up to 4200mAh / g, but the main reason why silicon electrode materials cannot be commercialized is that when lithium ions and silicon form a lithium-silicon alloy phase, the volume will expand to 300 to 400% of the original volume. This dramatic volume expansion will cause the silicon to pulverize and break and then separate from the plate, resulting in capacity loss and a poor cycle life. The theoretical gram capacity of silicon oxide is 1547mAh / g. Although it is not as high as the capacity of silicon, it has a smaller volume expansion (about 134%) and has a better gram capacity maintenance rate. The present invention can oxidize the surface layer of silicon into a silicon oxide layer by adding a trace amount of alkaline solution, thereby inhibiting the volume expansion of silicon and increasing the gram capacity maintenance rate.
[0037] In the present embodiment, the alkali solution is a lithium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution, and the pH value is 8 to 13. In some embodiments, the amount of alkali solution added may be, for example, 0.1 to 5 parts by weight based on 100 parts by weight of silicon nanoparticles. In other embodiments, preferably, the amount of alkali solution added may be, for example, 0.5 to 2 parts by weight. The amount of alkali solution added is related to the thickness of the surface silicon oxide layer of silicon nanoparticles for batteries. When the amount of alkali solution added is less than 0.1 parts by weight, the oxidation effect on silicon nanoparticles is almost negligible. When the amount of alkali solution added is greater than 5 parts by weight, the thickness of the silicon oxide layer formed will increase (more silicon is oxidized). Although the volume expansion of the silicon in the inner core can be effectively suppressed, the gram capacity of silicon oxide is less than the gram capacity of silicon, so that the gram capacity of the silicon-doped electrode material formed subsequently is significantly reduced. When the amount of alkali solution added is within the above range, the silicon-doped electrode material can have both high gram capacity and excellent gram capacity maintenance rate. At this time, the ratio of the particle size of the silicon nanoparticles for the battery to the thickness of the silicon oxide layer may be, for example, 3:1 to 40:1.
[0038] The silicon nanoparticles for batteries of the present invention can be mixed with electrode active materials to form silicon-doped electrode materials. Specifically, the method for manufacturing silicon-doped electrode materials may include the following steps: providing silicon nanoparticles for batteries of the present invention. Next, mixing silicon nanoparticles for batteries and active materials. Then, spray granulation and calcination are performed to obtain silicon-doped electrode materials. In some embodiments, the active material may be, for example, a carbon material, a metal element or a metal compound. Among them, the carbon material may be, for example, graphite or other carbon sources, the metal element may be, for example, tin, nickel, titanium, manganese, copper or magnesium, and the metal compound may be, for example, titanium carbide or titanate, but the present invention is not limited thereto.
[0039] The silicon-doped electrode material can be used as the negative electrode of the battery. The calcination step is performed after the inert gas is introduced, wherein the inert gas can be, for example, argon gas, and the calcination temperature can be, for example, 700 to 900 degrees. In the present invention, the dispersant / organic matter can be effectively cracked and removed through the calcination step to avoid affecting the electrical properties of the electrode material. In some embodiments, the content of silicon nanoparticles for batteries is 1 to 40% by weight based on the total weight of the silicon-doped electrode material. When the content of silicon nanoparticles for batteries is less than 1% by weight, due to the small content, it is equivalent to undoped silicon, so that the effect of improving the gram capacitance of the electrode material is not good. When the content of silicon nanoparticles for batteries is greater than 40% by weight, the stability of the battery may decrease.
[0040] The silicon nanoparticles for batteries of the present invention are described in detail below by way of examples. However, the following examples are not intended to limit the present invention.
[0041] Example
[0042] In order to prove that the silicon nanoparticles for batteries proposed in the present invention can effectively maintain the gram capacity of the electrode, this example is specifically described below.
[0043] Example 1: Relationship between the particle size of silicon nanoparticles, dispersant content, and grinding time
[0044] [Preparation of silicon nanoparticles for batteries]
[0045] Dispersants (polyethylene glycol and polyvinyl pyrrolidone) are dissolved in water to form a dispersion. Then, the dispersion and grinding media are fed into a grinder, and silicon raw materials are added for grinding to form silicon nanoparticles. Then, the ground silicon dispersion is unloaded and taken out, and a trace amount of alkali solution (lithium hydroxide) is added for mixed reaction to obtain silicon nanoparticles for batteries of Examples 1-5. The addition amounts of silicon raw materials, dispersants, grinding media and alkali solution and the grinding time are shown in Table 1.
[0046] [Measurement and results of average particle size]
[0047] The average particle size (D 50 ), and the results are shown in Table 1.
[0048] Table 1
[0049]
[0050]
[0051] It can be seen from Table 1 that as the amount of dispersant added increases and the grinding time increases, the average particle size of the ground silicon nanoparticles gradually decreases.
[0052] Example 2: Elemental analysis of silicon-doped carbon electrode materials
[0053] [Preparation of silicon-doped carbon electrode materials]
[0054] The silicon nanoparticles for battery (in a dispersion) of Example 1 were mixed with graphite and then spray granulated. Then, an inert gas (argon) was introduced and calcined to obtain the silicon-doped carbon electrode material of Example 6.
[0055] [TEM-EDS analysis and results]
[0056] The silicon-doped carbon electrode material of Example 6 was sliced and analyzed for structural elements using transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDS). The results are as follows: Figure 2A and Figure 2B shown.
[0057] Figure 2A For electronic images, Figure 2B for Figure 2A Elemental composition analysis results of the circled area. Please also refer to Figure 2A and Figure 2B The silicon content is relatively high compared to the oxygen content, and the silicon lattice image can be seen under high-resolution images, which further indicates that silicon is only partially oxidized and that carbon and silicon are a composite structure of alternating stacks.
[0058] Example 3: Capacity maintenance rate of silicon-doped carbon negative electrode half-cell
[0059] [Half-cell assembly]
[0060] The silicon-doped carbon negative electrode material containing silicon nanoparticles with different oxidation degrees for batteries is mixed with a conductive agent, an adhesive, and a solvent, and coated on a current collector, and then dried, rolled, and cut into silicon-doped carbon electrodes (negative electrode sheets) of the comparative example, Example 7, and Example 8, and then half-cells are assembled with lithium metal, a separator, and an electrolyte. In Example 7 and Example 8, the doping amount of silicon nanoparticles for batteries is 20% by weight of the silicon-doped carbon negative electrode material.
[0061] [Analysis and results of gram capacity]
[0062] Activation test
[0063] The silicon-doped carbon negative electrode half-cell was charged and discharged three times at a constant current charge and discharge rate of 0.1C. The first discharge gram capacity, first charge gram capacity and first coulombic efficiency were obtained from the first cycle data. The results are shown in Table 2.
[0064] Cycle life test
[0065] The silicon-carbon negative electrode half-cell was charged and discharged 200 times at a constant current charge and discharge rate of 0.5C, and the capacity retention rate was calculated. The results are shown in Table 2.
[0066] Table 2
[0067]
[0068] It can be seen from Table 2 that when the silicon surface does not have a silicon oxide film (comparative example), the first discharge / charge gram capacity of the silicon-doped carbon electrode formed therefrom is higher than that of the silicon-doped carbon electrodes of Examples 7 and 8 in which a silicon oxide film is present on the silicon surface. This is because the gram capacity of silicon oxide is lower than that of silicon, so after carbon is doped to form an electrode, the overall gram capacity will be lower. In addition, it can be seen from Table 2 that after 200 charge and discharge cycles, the capacity maintenance rate of the silicon-doped carbon electrodes of Examples 7 and 8 (with a silicon oxide film on the silicon surface) is higher than the capacity maintenance rate of the silicon-doped carbon electrode of the comparative example (without a silicon oxide film on the silicon surface), and the capacity maintenance rate is related to the thickness of the silicon oxide film on the silicon surface, indicating that the silicon oxide film on the silicon surface can effectively suppress the volume expansion of the silicon core.
[0069] In summary, in the manufacturing method of silicon nanoparticles for batteries of the present invention, the addition of dispersant can make silicon nanoparticles less likely to aggregate and agglomerate, avoid excessive stickiness that affects grinding, and promote the miniaturization of silicon raw materials; the addition of alkali solution can make the surface of silicon nanoparticles for batteries have a silicon oxide film, which can inhibit the volume expansion of silicon nanoparticles for batteries. The silicon-doped electrode material prepared by silicon nanoparticles for batteries of the present invention can effectively improve its gram capacity maintenance rate under multiple charge and discharge cycles.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for producing silicon nanoparticles for batteries, characterized in that: include: mixing a dispersant and a solvent to form a dispersion; Adding the dispersion, grinding media and silicon raw material into a grinder; Performing a grinding process to form silicon nanoparticles having an average particle size of less than 200 nanometers; Taking out the silicon dispersion containing the silicon nanoparticles; as well as Alkaline solution is added into the silicon dispersion to form silicon nanoparticles for batteries, wherein the surface layer of the silicon nanoparticles for batteries is a silicon oxide layer.
2. The manufacturing method according to claim 1, characterized in that: The silicon raw material is recycled silicon material.
3. The manufacturing method according to claim 1, characterized in that: The dispersant is at least one selected from polyethylene glycol, polyvinyl oxadiazole, triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide and fatty acid polyethylene glycol ester.
4. The manufacturing method according to claim 1, characterized in that: The solvent is water, an alcohol solvent or a ketone solvent.
5. The manufacturing method according to claim 1, characterized in that: Based on 100 parts by weight of the silicon raw material, the dispersant added to the grinder is added in an amount of 10 to 50 parts by weight.
6. The manufacturing method according to claim 1, characterized in that: The grinding media is spherical in shape and has an average particle size of 100 to 500 nanometers.
7. The manufacturing method according to claim 1, characterized in that: Based on 100 parts by weight of the silicon raw material, the grinding media is added in an amount of 100 to 500 parts by weight.
8. The manufacturing method according to claim 1, characterized in that: The alkali solution is a lithium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution.
9. The manufacturing method according to claim 1, characterized in that: Based on 100 parts by weight of the silicon nanoparticles, the amount of the alkali solution added is 0.1 to 5 parts by weight.
10. The manufacturing method according to claim 1, characterized in that: The grinding process is a wet ball milling method, and the grinding time is 2 to 6 hours.
11. The manufacturing method according to claim 1, characterized in that: The ratio of the particle size of the silicon nanoparticles for batteries to the thickness of the silicon oxide layer is 3:1 to 40:
1.
12. The manufacturing method according to claim 1, characterized in that: The thickness of the silicon oxide layer is 5 to 30 nanometers.
13. A method for manufacturing a silicon-doped electrode material, characterized in that: include: Providing silicon nanoparticles for batteries obtained by the manufacturing method according to any one of claims 1 to 12; mixing the silicon nanoparticles for battery with active materials; as well as Performing spray granulation and calcination to obtain the silicon-doped electrode material, The active material is a carbon material, a metal element or a metal alloy compound.
14. The manufacturing method according to claim 13, characterized in that: The content of the silicon nanoparticles for battery is 1 to 40 weight % based on the total weight of the silicon-doped electrode material.
